Evaluation of Clinical Profiles in Patients with Benign Pituitary Tumors - Aleksandra Marković; Tamara Dojčinović; Milena Brkić; Tamara Popović Perić (Биомедицинска истраживања, 2025)
Introduction: Benign pituitary tumors are a heterogeneous group of neoplasms with varying clinical presentations depending on their hormonal activity, size, and mass effects. These tumors can cause significant morbidity due to endocrine dysfunction and compression of adjacent structures. Understanding their clinical characteristics is essential for improving diagnostic accuracy, optimizing treatment strategies, and predicting complications. This study aimed to evaluate the clinical profiles of patients with benign pituitary tumors, focusing on demographic characteristics, hormonal activity, and tumor size. Methods: This retrospective five-year study (2019-2023) conductedat the University Clinical Center of Republic of Srpska, Banja Luka included patients diagnosed with benign pituitary tumors who underwent clinical, biochemical, and radiological evaluations. Demographic data, hormonal profiles, and tumor dimensions assessed via MRI were analyzed. Tumors were classified as functioning or non-functioning based on hormonal secretion. Statistical analysis explored associations between clinical parameters and tumor characteristics. Results: This study analyzed data from patients diagnosed with benign pituitary gland neoplasms. The mean patient age was 48.61 years (SD = 17.60), ranging from 20 to 85 years. Among 53 patients with available tumor functionality data, 79.2% had functional adenomas, with prolactinomas being the most common (64.1%). Macroadenomas were present in 58.0% of cases, and 22.4% of tumors were invasive. Surgery was performed in 21 patients, with 76.2% undergoing transsphenoidal surgery. Remission was achieved in 5.9%, and complete resection in 17.7%. Conclusions: A comprehensive assessment of clinical features in benign pituitary tumors is essential for tailoring individualized treatment and improving patient outcomes.
Keywords: pituitary tumors; benign neoplasms; hormonal activity; clinical characteristics; endocrine dysfunction; tumor classification